(untitled) (Strathmore Law Review, 2023)
After over a decade of extensive work, the Supreme Court of Kenya has built a substantial track record. Consequently, a thorough appraisal of the judges’ efforts is undoubtedly warranted, given the Court’s crucial role in safeguarding democracy and upholding the rule of law in Kenya. How judges go about deciding cases has consistently attracted considerable scrutiny. Moreover, in the study of judicial behaviour, there are various considerations as to which factors affect the outcomes of judicial decisions. Judicial philosophy, being one such factor, is a chosen, articulable, and rationally defensible method of judicial decision-making that generally includes an explicitly articulated view of many legal concepts, including separation of powers. This paper conducts a hermeneutic analysis of Supreme Court cases to investigate the judicial philosophy of the Supreme Court regarding the concept of separation of powers and evaluate its appropriateness for the post-2010 constitutional dispensation. It is argued that the philosophy the Court has adopted is not clear-cut, it is comprised of excessive restraint and sporadic overreach. Consequently, it is proposed that the Court should embrace transformative prudentialism as a philosophy because unlike judicial restraint or judicial activism, it is not tied down to determined actions irrespective of the circumstances, it seeks to meet the aims of transformative constitutionalism.